The Relationship Between Learning Methods and Students’ Achievement in Tajwid at TPQ Nurul Jannah, Koto Baru, Dharmasraya - Randa Gempa Saputra; Lili Dasa Putri (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2026)
This research was motivated by the low Tajwid learning outcomes of students at TPQ Nurul Jannah, Koto Baru Dharmasraya. This problem is assumed to be influenced by the learning methods used in the learning process. This study aims to (1) describe the learning methods used in Tajwid instruction, (2) describe students’ Tajwid learning outcomes based on educators’ assessments, and (3) determine the relationship between learning methods and students’ Tajwid learning outcomes at TPQ Nurul Jannah. This research is a quantitative correlational study. The population consisted of 46 students, while the sample consisted of 32 students selected using cluster random sampling. Data on learning methods were collected using a validated Likert-scale questionnaire covering four aspects: people, learning objectives, learning materials, and time and facilities. Learning outcome data were obtained from teachers’ assessment records. Data analysis used percentage formulas and Product Moment correlation. The results show that learning methods are still in the low category, students’ Tajwid learning outcomes are relatively low, and there is a significant relationship between both variables. Therefore, teachers are recommended to improve the variety and effectiveness of learning methods, and TPQ management should support adequate facilities. Future research is suggested to expand variables and context.